2001
DOI: 10.1086/318787
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Penetrance of Germline BRCA1 and BRCA2 Mutations in a Population Series of 649 Women with Ovarian Cancer

Abstract: A population-based series of 649 unselected incident cases of ovarian cancer diagnosed in Ontario, Canada, during 1995-96 was screened for germline mutations in BRCA1 and BRCA2. We specifically tested for 11 of the most commonly reported mutations in the two genes. Then, cases were assessed with the protein-truncation test (PTT) for exon 11 of BRCA1, with denaturing gradient gel electrophoresis for the remainder of BRCA1, and with PTT for exons 10 and 11 of BRCA2. No mutations were found in all 134 women with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
575
11
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 907 publications
(642 citation statements)
references
References 35 publications
38
575
11
18
Order By: Relevance
“…These observations are in agreement with large studies on ovarian cancer patients (Risch et al, 2001;Frank et al, 2002). It has repeatedly been shown that only a small percentage of BRCA-positive ovarian cancer cases occur at ages o40 years (Boyd et al, 2000;Liede et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…These observations are in agreement with large studies on ovarian cancer patients (Risch et al, 2001;Frank et al, 2002). It has repeatedly been shown that only a small percentage of BRCA-positive ovarian cancer cases occur at ages o40 years (Boyd et al, 2000;Liede et al, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Germline BRCA2 mutations predispose to hereditary breast and ovarian cancer. In some families with BRCA2 mutations, an increased incidence of GC has been encountered [40][41][42][43], with one family fulfilling the HDGC criteria [35].…”
Section: Genetics Of Hdgcmentioning
confidence: 99%
“…Breast cancer affects males as well as females, and there is no apparent postmenopausal decline in breast cancer risk. In one recent study, the risks of all cancers combined were similar for male and female relatives of BRCA2 mutation carriers (Risch et al, 2001). To date, most of the preventive strategies have been based on estrogen blockade, but there is emerging evidence that antioxidants may be a complementary route of prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Other methods are used which depend on the reporting of cancers by family members. The lifetime risk of breast cancer in women who carry a deleterious BRCA1 or BRCA2 mutation is estimated to be as high as 80% -or roughly 10 times greater than that of the general population -but several estimates are lower (Ford et al, 1998;Risch et al, 2001;Antoniou et al, 2003;King et al, 2003). In a cohort of 76 BRCA1 mutation carriers from Rotterdam, eight invasive cancers were detected during 318 person-years of follow-up (Meijers-Heijboer et al, 2001) -an annual incidence of 2.5%.…”
Section: Introductionmentioning
confidence: 99%